Impact of family social support on Yemeni female employee turnover intention - Abdulkader, Ghamdan; M, Rakesh Krishnan (Edelweiss Applied Science and Technology, 2025)
The purpose of this study is to gain a better understanding of how providing women with both emotional and practical support might mitigate work-family conflict (WFC) and, in turn, reduce the likelihood that they will leave their current places of employment. We used convenience sampling to survey female educators in the private school sector in Sana’a, Yemen, to learn more about their experiences with and perspectives on WFC. SPSS 23 and PLS 4 were used in conjunction with other statistical packages to conduct in-depth analyses of the acquired data. According to the findings, providing emotional support has a negative effect on WFC, while providing material support does not significantly aid in resolving challenges associated with WFC. WFC was also found to be significantly associated with resignation intent. As a tool for studying direct and mediated links across multiple dimensions, the WFC model described here is particularly useful for studies focusing on women in the workforce. By taking a more narrow focus to examine the experiences of women in the workplace, this study contributes significantly to our knowledge of WFC compared to earlier studies. As a result, this study adds significantly to the body of prior work in the field.